Refractrometic Studies of Binary Mixtures of Flavoured Compounds and Some Hydrocarbons - Yadav, Neetu; Arfin, Tanvir; Yadav, S. S. (Journal of Applied Solution Chemistry and Modeling, 2013)
Refractive indices have been measured for the binary liquid mixtures of n-butylethanoate and 3- methylethanoate with cyclohexane, benzene, 1,4-dimethylbenzene and 1,3,5-trimethylbenzene over the entire composition range at 308.15K . From the experimental data, the values of deviation in refractive index (Δn), molar refraction (R) and deviation in molar refraction (ΔR) have been determined. The values of Δn and ΔR have been fitted to the Redlich Kister polynomial equation to determine the standard deviation.